Integrating Episodic Future Thinking into Virtual Reality to Mitigate Substance Use Disorders: A Theoretical Framework. (November 2019) - Wang, Tianzi; Mellis, Alexandra M.; Lau, Nathan; Bickel, Warren
Substance use disorders present major health risks and economic burdens, while current healthcare systems face insufficient resources and accessibility deficiencies that challenge long term treatment for chronic diseases. This paper presents a theoretical approach of integrating the concept of episodic future thinking into immersive virtual reality to treat substance use disorders. Episodic future thinking can extend the temporal window over which an individual values rewards, rebalancing the impulsive and executive decision systems and thereby reducing the valuation of substances of abuse. In theory, virtual reality can enhance episodic future thinking by providing realistic cues and contexts. We propose using schema theory to guide the design of virtual reality for facilitating episodic future thinking. Future work should focus on developing and evaluating a proof-of-concept of this theoretical framework.